Geometri Fraktal Dengan Pemrograman Java - Fiska Kusuwawati; palgunadi .; dahlan susilo (Universitas Sahid Surakarta, 2009)
Fractal geometry is branch of mathematics that studies the properties and behavior of fractal. In development fractal is branch of computer grpaphics. In this examination, fractal is discussi to develop computer graphics. The development does with literature and simulation based on former of each the curve. There are four fractal will be discussied in this examination, Koch curves, String Grammars, Julia and Mandelbrot Set. Koch curves are formed from line and angel rotation (α). For String Grammars the former of component is curve sentence, formulated with F : (axiom, F-string, f-string, X-string, Y-string, sudut). Mandelbrot and Julia Set are generation a set of complex number zn+1= z n2 + c. Where c belongs to the set of all complex numbers. Koch curve has a good curve if it has special angel (300, 450, 600) except 900. Example ofproduct from String Grammars are Dragon, Hilbert, Sierpinski, Island, Tree1, Tree2, and Tree3. Madelbrot and Julia Set has good curve if it has z coefficient among -2 up to 2 for Real and -2 up to 2 for the Imaginer and the number of iteration is bigger then 50, and the constant |c| is less then 1.